2018
DOI: 10.1016/j.molstruc.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and antimicrobial activity of some nickel, cadmium and mercury complexes of 5-methyl pyrazole-3yl-N-(2′-methylthiophenyl) methyleneimine, (MPzOATA) ligand

Abstract: , characterization and antimicrobial activity of some nickel, cadmium and mercury complexes of 5-methyl-3yl-N-(2´-methylthiophenyl)methyleneimine, (MP z OATA) ligand

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…Although the present study does not show any direct experimental evidence about the mechanism of antibacterial activity of the Co and Ni complexes, it can be corroborated with our previous observation of membrane damage as inflicted by some Ni, Cd and Hg complexes against Gram positive (Bacillus subtilis 6633) and Gram negative (Proteus vulgaris OX19) bacterial strain [77].…”
Section: Antimicrobial Activitysupporting
confidence: 88%
“…Although the present study does not show any direct experimental evidence about the mechanism of antibacterial activity of the Co and Ni complexes, it can be corroborated with our previous observation of membrane damage as inflicted by some Ni, Cd and Hg complexes against Gram positive (Bacillus subtilis 6633) and Gram negative (Proteus vulgaris OX19) bacterial strain [77].…”
Section: Antimicrobial Activitysupporting
confidence: 88%
“…Co(II), Ni(II), and Zn(II) complexes did not show such signicant antimicrobial activity. 37 Similar discrepancies in the antimicrobial activity were observed by Mandal et al 37 who described a strong biostatic effect of cadmium and mercury complexes of 5-methyl pyrazole-3yl-N-(20-methylthiophenyl) methyleneimine, (MPzOATA) ligand, against some Gram-positive and Gram-negative bacteria, while nickel complexes with the same ligands (…”
Section: Crystal Structuresmentioning
confidence: 53%
“…Recently, Mondal et al reported the syntheses and antimicrobial activity of some Ni(II), Cd(II) and Hg(II) complexes of a pyrazole containing Schiff base ligands. The results showed that the complex 207 demonstrated highest antimicrobial agents against both Gram positive and Gram negative bacteria [ 111 ]. A series of isoxazolyl thiazolyl pyrazoles were synthesized by Mor et al and evaluated in vitro for antimicrobial activity.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%